NILAI PENDIDIKAN WANITA DALAM SURAT AL-AHZAB AYAT 28-35 DAN AYAT 59 SERTA APLIKASINYA DALAM PENDIDIKAN ISLAM - Saipon, Abdul; Hafidhuddin, Didin; Syafri, Ulil Amri (Tawazun: Jurnal Pendidikan Islam, 2019)
This study aims to find out the value of women's education in the letters of al-Ahzab verses 28-35 and 59, and apply it in Islamic Education. In this study, the author uses the maudhu'i interpretation method, which is to study the verses in various ways and to perform the analysis based on the correct knowledge used to explain the subject matter, so that they can easily understand the issues and meanings of the verses. The source that the researcher used was the interpretation of al-Azhar by Prof. Dr. Hamka and interpretations of Jalaluddin Asy-Syuyuthi and Muhammad Ibn Ahmad Al-Mahali's writings. As for the value of women's education in the letters of al-Ahzab verses, 28-35 and verse 59 of its application in Islamic education is: One, moral education. Moral education can be achieved with qonaat behavior, always at home, honest, patient, and honorable. Two, worship education. Religious education can be performed with Sholeh deeds, prayers, giving alms, obeying Allah and His Messenger, reading the Qur'an, fasting and wearing a veil. Three, creed education. Faith education can be achieved through the practice of Zikirullah (in remembrance of Allah S.W.T.) Abstrak Penelitian ini bertujuan untuk mengetahui nilai pendidikan wanita dalam surat al-Ahzab ayat 28-35 dan 59, serta aplikasikannya dalam Pendidikan Islam. Dalam penelitian ini, penulis menggunakan metode tafsir maudhu'i, yaitu dengan cara meneliti ayat-ayat dari berbagai segi, dan melakukan analisis berdasarkan ilmu yang benar yang digunakan untuk menjelaskan pokok permasalahan, sehingga dapat memahami permasalahan dan maksud ayat-ayat tersebut dengan mudah. Adapun sumber yang peneliti pakai adalah tafsir al-Azhar karangan Prof. Dr. Hamka dan tafsir Jalalain karangan Jalaludin Asy-Syuyuthi dan Jalaludin Muhammad Ibn Ahmad Al-Mahali. Adapun nilai pendidikan wanita dalam surat al-Ahzab ayat 28-35 dan ayat 59 aplikasinya dalam pendidikan Islam yaitu: Satu, pendidikan akhlak. Pendidikan akhlak dapat ditempuh dengan perilaku qonaat, selalu tetap di rumah, jujur, sabar, dan menjaga kehormatan. Dua, pendidikan ibadah. Pendidikan ibadah dapat ditempuh dengan amal Sholeh, shalat, mengeluarkan zakat, taat kepada Allah dan Rasul, membaca Al-Qur'an, berpuasa dan memakai jilbab. Tiga, pendidikan akidah. Pendidikan akidah dapat ditempuh dengan amalan Zikirullah (mengingat Allah S.W.T.)